WHO 2016 classification of gliomas - Wesseling, Pieter; Capper, David (Neuropathology & applied neurobiology, 2018)
Gliomas are the most frequent intrinsic tumours of the central nervous system and encompass two principle subgroups: diffuse gliomas and gliomas showing a more circumscribed growth pattern (‘nondiffuse gliomas’). In the revised fourth edition of the WHO Classification of CNS tumours published in 2016, classification of especially diffuse gliomas has fundamentally changed: for the first time, a large subset of these tumours is now defined based on presence/absence of IDH mutation and 1p/19q codeletion. Following this approach, the diagnosis of (anaplastic) oligoastrocytoma can be expected to largely disappear. Furthermore, in the WHO 2016 Classification gliomatosis cerebri is not an entity anymore but is now considered as a growth pattern. The most important changes in the very diverse group of ‘nondiffuse’ gliomas and neuronal-glial tumours are the introduction of anaplastic pleomorphic xanthoastrocytoma, of diffuse leptomeningeal glioneuronal tumour and of RELA fusion-positive ependymoma as entities. In the last part of this review, after very briefly touching upon classification of neuronal, choroid plexus and pineal region tumours, some practical implications and challenges associated with the WHO 2016 Classification of gliomas are discussed.
First published: 16 August 2017
Gesehen am 23.04.2020